Transcriptional responses of Leishmania (Leishmania) amazonensis in the presence of trivalent sodium stibogluconate (2019)
Background: In the last decade, resistance to antimonials has become a serious problem due to the emergence of drug-resistant strains. Therefore, understanding the mechanisms used by Leishmania parasites to survive under drug pressure is essential, particularly for species of medical-veterinary importance such as L. amazonensis. Methods: Here, we used RNA-seq technology to analyse transcriptome profiles and identify global changes in gene expression between antimony-resistant and -sensitive L. amazonensis promastigotes. Results: A total of 723 differentially expressed genes were identified between resistant and sensitive lines. Comparative transcriptomic analysis revealed that genes encoding proteins involved in metabolism (fatty acids) and stress response, as well as those associated with antimony resistance in other Leishmania species, were upregulated in the antimony-resistant line. Most importantly, we observed upregulation of genes encoding autophagy proteins, suggesting that in the presence of trivalent stibogluconate (SbIII) L. amazonensis can activate these genes either as a survival strategy or to induce cell death, as has been observed in other parasites. Conclusions: This work identified global transcriptomic changes in an in vitro-adapted strain in response to SbIII. Our results provide relevant information to continue understanding the mechanism used by parasites of the subgenus Leishmania (L. amazonensis) to generate an antimony-resistant phenotype. © 2019 The Author(s).